Integrating Qur’anic and Prophetic Values into Islamic Education Curriculum Development in the Age of Disruption - Nany Kholilah; Mufatihatut Taubah (Jurnal test, 2026)
This research aims to analyze the integrative strategies of the values of the Qur’an and Hadith in the development of the Islamic education curriculum in the era of modern disruption. This research uses a qualitative-descriptive approach with a library research method. Research data were obtained from the text of the Qur’an, the hadith of the Prophet, classical and contemporary tafsir books, Islamic Religious Education curriculum documents such as the 2013 Curriculum and the Independent Curriculum, as well as various relevant scientific literature. The analysis was carried out through a thematic approach to identify the educational values in the Qur’an and Hadith and examine their relevance to the development of the Islamic education curriculum in the digital era. The results of the study show that the integrative strategy in the development of the Islamic education curriculum includes three main dimensions, namely strengthening teachers’ digital literacy as a prerequisite for contextual learning, the application of the Living Qur’an approach that connects the text of revelation with the social reality of students, and the development of inclusive pedagogy that respects the diversity of student characteristics. In addition, the recontextualization of the Prophet’s educational methods such as exemplary (uswah hasanah), dialogue, and gradual learning (tadarruj) shows a strong relevance to the modern pedagogical paradigm centered on students. This study emphasizes that the transformation of the Islamic education curriculum will only be effective if the integration of Qur’anic and Prophetic values is carried out systematically in curriculum design, pedagogical strategies, and a sustainable educational ecosystem.